The Jaguar's Dream - Kinsella, John (Alma Books, 2012)
A new collection from this brilliant Australian poet. In this volume of 'cover' poems, John Kinsella takes the work of poets from across the centuries writing in languages other than English, including French, Russian, German, Greek, Latin and Chinese, and recreates the original works as translations, adaptations and versions. In the case of nineteenth-century French poets, including Leconte de Lisle, Charles Baudelaire, Arthur Rimbaud and Charles Cros, there is close consideration of the traditional conventions of translation; Kinsella produces versions designed to capture the intent and design of the originals. However, with medieval poet Francois Villon, Kinsella has taken his 'criminal jargon' poems and made radical departures into a play on contemporary criminal' language. Using a vast array of interpretative techniques, Kinsella takes the reader from the intense and chthonic animal poems of the Parnassian Leconte de Lisle, who spent much of his younger life on his birth island of Bourbon (La Reunion), through linguistically innovative remakings of Tristan Tzara's Dadaist poetry, to enigmatic investigations of the brilliant twentieth-century poet of witness, fragmentation and reconstitution of language, Paul Celan.